Pediatric Acute Myeloid Leukemia (AML): From Genes to Models Toward Targeted Therapeutic Intervention - Mercher, Thomas; Schwaller, Juerg (Frontiers in Pediatrics, 2019)
This review aims to provide an overview of the current knowledge of the genetic lesions driving pediatric acute myeloid leukemia (AML) and emerging biological concepts and strategies for therapeutic intervention. Hereby we focus on lesions that are preferentially or exclusively occurring in pediatric patients, and molecular markers of aggressive disease with often poor outcome including fusion oncogenes that involve epigenetic regulators like KMT2A, NUP98 or CBFA2T3, respectively. Functional studies were able to demonstrate functional cooperation with signaling mutations leading to constitutive activation of FLT3 or the RAS signal transduction pathways. We discuss the issues faced to faithfully model pediatric acute leukemia in mice. Emerging experimental evidence suggests that the disease phenotype is dependent on the appropriate expression and activity of the driver fusion oncogenes during a particular window of opportunity during fetal development. We also highlight biochemical studies that deciphered some molecular mechanisms of malignant transformation by KMT2A, NUP98 and CBFA2T3 fusions, which in some instances allowed to develop small molecules with potent anti-leukemic activities in preclinical models (e.g. inhibitors of the KMT2A-MENIN interaction). Finally, we discuss other potential therapeutic strategies that not only target driver fusion-controlled signals but also interfere with the transformed cell state either by exploiting the primed apoptosis or vulnerable metabolic states or by increasing tumor cell recognition and elimination by the immune system.